Application of Super Item Learning Model in Improving Learning Outcomes of Photosynthesis Concept in Class VIII of SMP Al-Wathan Ambon - Junardin Muhamad Masihu; Edi Masihu (Lembaga Intelektual Muda (LIM) Maluku, 2022)
The super item learning model is one of the learning models that is oriented towards understanding and activeness of students in problem solving. This type of research is descriptive with the aim of determining whether the application of the Super ITEM model in improving the learning outcomes of the concept of photosynthesis in class VIII2 of SMP AL-Wathan Ambon. The sample in this study was 29 people. The instruments used are tests, affective observation sheets, and psychomotor observation sheets. The data analysis used is descriptive data analysis of student learning outcomes, affective observation results, and student psychomotor. The results of data analysis obtained the learning process using a super item learning model students are more active in the learning process when compared to the learning process that is carried out conventionally. These results can be seen from the classical average score obtained, namely in the initial test implementation, the average score obtained was 47.37 and increased in the implementation of the final test, whose average score obtained was 75.40. Based on the results of learning completion using a super item learning model, students who achieved a minimum completion standard of 23 people or with a percentage of 79.31 percent.